2009
DOI: 10.1590/s0482-50042009000500007
|View full text |Cite
|
Sign up to set email alerts
|

Consenso de imunização para crianças e adolescentes com doenças reumatológicas

Abstract: Incidence of infectious diseases is higher in children and adolescents with rheumatic diseases than in the general population due to disease activity, possible immune deficiency secondary to the disease itself, or the use of immunosuppressive drugs. Vaccination is effective in reducing morbidity and mortality in those patients. The objective of this study was to establish an evidence-based consensus on the efficacy and safety of vaccination in children and adolescents with rheumatic diseases. Passive immunizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 60 publications
0
4
0
6
Order By: Relevance
“…Several publications discuss indications of special immunobiologicals or describe the care to specific groups in the CRIE 3 , 5 , 6 , 21 , 24 , 26 , but we did not find studies that evaluate the implementation of CRIE in national perspective.…”
Section: Introductionmentioning
confidence: 75%
“…Several publications discuss indications of special immunobiologicals or describe the care to specific groups in the CRIE 3 , 5 , 6 , 21 , 24 , 26 , but we did not find studies that evaluate the implementation of CRIE in national perspective.…”
Section: Introductionmentioning
confidence: 75%
“…According to this consensus, it was concluded that there are few studies on efficacy and safety of using vaccines for these diseases in pediatric patients. 8 According to the American Academy of Pediatrics, immunization with live vaccine component is contraindicated when prednisone is used in doses equal to or greater than 2 mg/kg or higher than 20 mg/day, for longer than a week. 14 The Committee of Immunization Practices of the CDC instructs that live agents vaccines can be used in patients on MTX at doses ≤ 0.4 mg/kg/week or 28 mg/week in an individual with 70 kg, azathioprine ≤ 3 mg/kg/day, or 6-mercaptopurine ≤ 1.5 mg/kg/day.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our concern with these issues was highlighted in a systematic review of medical literature on efficacy and safety of vaccines in children and adolescents with rheumatic diseases based on levels of scientific evidence. 8 This consensus demonstrated the safety and efficacy of inactivated vaccines and protein components against virus, such as hepatitis A and B, influenza, pneumococcus, meningococcus, Haemophilus, Salk, and tetanus, in patients with rheumatic diseases, despite the use of immunosuppressive drugs. Furthermore, this review suggested that vaccination with live agents against yellow fever, BCG, rotavirus, varicella, polio, and MMR are contraindicated in immunosuppressed patients.…”
Section: Introductionmentioning
confidence: 97%
“…Chaves et al (2008) As piores taxas de cobertura, a exemplo do que foi observado no presente estudo, foram para hepatite B, varicela e vacina pneumocócica (CHAVES et al, 2008). (BOSCH et al, 2006;WALLACE;HAHN, 2007) e/ou uso de imunossupressores, no caso de vacinas de componentes vivos atenuados (GLUCK et al, 2005;SILVA et al, 2009). Os pacientes com LES apresentaram a maior porcentagem de atraso vacinal secundário à contraindicação médica (40%), o que seria esperado, já que esses pacientes freqüentemente usam medicamentos imunossupressores.…”
Section: Discussionunclassified
“…Schneeweiss et al (2007) MAILLEFERT et al, 1999;POPE et al, 1998;TOUSSIROT et al, 2000). BSR, 2002;HARPER et al, 2005;SILVA et al, 2009;SMITH et al, 2006).…”
Section: Doenças Reumáticas E O Risco De Infecçõesunclassified